Analisis Pengaruh Tingkat Suku Bunga Dan Jangka Waktu Pinjaman Terhadap Permintaan Kredit Pada Koperasi Unit Desa Periode 2020-2024 - Mellya Nawang Kinasih; Viras Alti Pidola (Journal of Islamic Economic and Law (JIEL), 2025)
Village Unit Cooperatives (KUD) play a significant role in the rural economy of Indonesia, particularly by providing financial access to members who often face barriers in accessing formal financial institutions. One of the crucial functions of KUD is credit distribution, which enables members to develop micro-enterprises, agricultural activities, and fulfill consumptive needs. The interest rate is the compensation paid for the use of borrowed funds, while the loan term refers to the agreed period between the creditor and the debtor for repaying both principal and interest. Credit refers to the provision of money or claims that can be equated to money. This study aims to analyze the effect of interest rates and loan terms on credit demand at the KUD Mekar Abadi in Tasik Juang Village during the 2020–2024 period. Using a quantitative approach with multiple linear regression analysis, a sample of 78 respondents was selected from a population of 356 cooperative members. The regression test results indicate that both independent variables—interest rate and loan term—significantly affect credit demand. The t-test shows that the interest rate (X1) has a significance value of 0.000 with a t-value of 74.541 > t-table 1.992, while the loan term (X2) is also significant with a t-value of 4.175 > t-table. The F-test shows an F-value of 2786.918 > F-table 3.114 with a significance level of 0.000. The coefficient of determination (R²) is 0.987, indicating that 98.7% of the variation in credit demand is explained by the two variables. The data also passed the normality test and showed no signs of heteroscedasticity. These findings emphasize the importance of interest rate and loan term policies in influencing rural community credit demand.